Can the poor influence policy? : participatory poverty assessments in the developing world - Robb, Caroline M., 1963- (Washington, D.C. : World Bank, 1999)
Participatory Poverty Assessments (PPAs) use participatory research methods to understand poverty from the perspective of the poor by focusing on their realities, needs, and priorities. The principle of a PPA is to ensure that the intended beneficiaries have some control over the research process. Communities share their knowledge and are involved in analyzing the results. This book proposes a threefold classification of PPAs based on their varying impacts: 1) deepening our understanding of poverty; 2) influencing policy; and 3) strengthening policy implementation. There is no single model for PPAs. However, this book suggests some minimum standards and good practice for participatory policy research that aims to affect policy change. PPAs are highlighting the potentially powerful role the poor can play in analyzing poverty, developing interventions for its reduction, and assessing the impact of projects and policies. The challenge for the Bank and the rest of the development community is to effectively integrate the perspectives and values of the poor into the process of policy and project formulation and implementation
Includes bibliographical references (p. 67-72).
Keywords: Poor -- Research -- Developing countries; Poor -- Political activity; Poverty -- Research; Poor -- Attitudes